First steps toward a history of the Mid-Victorian novel in colonial Australia - Dolin, Tim (2006)
I am interested in a model of literary interpretation responsive to the spatial and temporal distances across which texts move. My approach is to use quantitative reading data to analyse the circulation of Victorian written culture in a range of Australian colonial contexts, and to construct from that analysis locally situated re-readings of well-known and lesser-known novels.